Determinants of Firm Value with Conditional Process Model: Evidence from Healthcare Sector Companies in Indonesia - Yulandri, Elsa; Sari, Maya; Waspada, Ikaputera (JURNAL AKUNTANSI, 2024)
This study aims to analyze the variables that affect the value of health sector companies in Indonesia, using the conditional process model with variables of Intellectual capital, IOS, DPR, Leverage, and firm size. The research method used is a descriptive method with a non-experimental quantitative approach. The population of this study was 30 health sector companies indexed on the IDX-IC Indonesia Stock Exchange. Furthermore, using a purposive sampling technique with the main criteria, nine companies were obtained as samples. Important findings in this study are that IOS is a predictor that has the strongest relative total effect on firm value, and IOS also plays a role in mediating the effect of intellectual capital and firm size on firm value. Next, leverage is found to moderate the effect of IOS on firm value positively. IOS optimization is influenced by intellectual capital. Thus, health sector companies must improve and manage intellectual capital well. Health sector companies can maximize their debt to invest in new products or expand the production of existing products. This provides theoretical implications for the firm value literature, where mediation and moderation models using IOS and Leverage in this research context are still limited.